Regulatory Barriers For Entrepreneurship and Start-Ups In Renewable Energy: Bibliometric Analysis - Iuliia Myroshnychenko; Serhiy Podosynnikov; Dmytro Halynskyi; Mykola Ushkalov; Oleksandr Chuhai (SocioEconomic Challenges)
This article conducts a bibliometric analysis to investigate regulatory barriers faced by entrepreneurs and start-ups in the renewable energy sector. The research highlights how inconsistent and outdated regulations in many regions challenge the growth and scalability of renewable energy ventures. Key barriers include complex permitting processes, restrictive grid connection policies, and inadequate support mechanisms such as subsidies and tax incentives. The study underscores that although global investment in renewable energy technologies has grown, many emerging and developing economies lag behind due to high capital costs and regulatory hurdles. The methodology involves data collection from the Scopus database using specified keywords such as "entrepreneurship," "start-ups," "renewable energy," and "regulatory barriers." One hundred seven documents published between 2002 and 2024 were analysed through bibliometric techniques using tools like Biblioshiny and Excel. The study cleans and processes data by removing irrelevant terms and consolidating synonyms to improve the accuracy of the bibliometric analysis. Key research indicators, such as the h-index, g-index, m-index, and citation rates, are employed to evaluate the impact of publications and authors. The analysis also focuses on co-citation networks, clustering keywords, and tracking the evolution of themes over time. Results reveal that regulatory barriers to renewable energy entrepreneurship are widely studied but fragmented. Five main keyword clusters were identified: renewable energy technologies, policy and regulatory frameworks, business models, economic development, and environmental sustainability. A notable trend is the convergence of interdisciplinary research, combining economic, policy, and technological perspectives on overcoming barriers. The analysis highlights a significant publication growth in recent years, peaking in 2022 with 15 publications, which reflects an increasing academic interest in this area. The most cited papers often discuss solutions to regulatory challenges, such as streamlining administrative processes, improving grid access, and implementing supportive financial mechanisms. Case studies from leading renewable energy markets, like Germany and California, showcase successful strategies that have fostered innovation and allowed start-ups to thrive. However, the study emphasises that many emerging markets continue to struggle with outdated regulatory frameworks that hinder the commercialisation of new technologies, particularly in energy storage. The study concludes that future research should focus on detailed longitudinal studies and interdisciplinary approaches that combine legal, economic, and technological analyses. Policymakers are urged to adopt flexible, adaptive regulations to support innovation in renewable energy, ensuring that start-ups can leverage technological advancements and contribute to the global energy transition.